(untitled) (Agroindustrial Science, 2024)
The aim of the following work was to evaluate a diet formulated with byproducts from the brewing and wine industry for lactating goats and quantify its potential in terms of nutritional quality and quantity. Twelve multiparous Nubian x Saanen goats, 2.75 years old (+ 1,24) during an experimental period of 12 weeks: 2 weeks of habituation and 10 weeks of testing. In both diets the goats grazed 6 hours on natural grass. Diet T0 (n = 6): Commercial feed: 500 g/day/goat (16% CP and 2.6 Mcal ME/kg DM) and diet T1 (n = 6): non-traditional balanced feed: 500 g/day/goat (16% CP and 2.6 Mcal ME/kg DM). Productive performance and health parameters were evaluated in goats fed with both diets during a period of 5 weeks starting 35 days postpartum. Total dry matter intake (DMI), milk production and corrected (MY and MYC), live weight (BW), body condition score (BCS), degree of FAMACHA© and quantitative coproparasitological diagnosis (EPG and OPG) were measured. A greater DMI was observed at T0 compared to T1 (p < 0.05). MY, MYC, BW, BCS, FAMACHA©, EPG and OPG did not show significant differences (p > 0.05) between both diets (T0 vs T1) throughout the experimental period evaluated. Goat health parameters throughout the study were within the physiological range during the production cycle and did not interfere with dietary treatments. The formulation of the diet with barley bagasse and grape pomace in dairy goats had a productive behaviour and health parameters like those of the commercial diet evaluated, without affecting milk production.